2009
DOI: 10.1007/s00442-009-1458-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of nutrient-limited primary production on primary, secondary or tertiary consumers

Abstract: Nutritional imbalances between predator and prey are the rule rather than the exception at the lower end of food webs. We investigated the role of different grazers in the propagation of nutritionally imbalanced primary production by using the same primary producers in a threetrophic-level food chain and a four-trophic-level food chain experimental setup. The three-trophic-level food chain consisted of a classic single-cell primary producer (Rhodomonas salina), a metazoan grazer (the copepod Acartia tonsa) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 60 publications
6
90
1
Order By: Relevance
“…The copepodites investigated in this present study showed increasing respiration rates with an increase of carbon in their food. Higher body-specific respiration rates in juvenile stages suggest that juvenile copepods use respiration to dispose of excess C as CO 2 and regulate their homoeostasis (He and Wang 2008;Laspoumaderes et al 2010;Darchambeau et al 2003), a pattern which has been reported from other juvenile zooplankton species (Jensen and Hessen 2007;Malzahn et al 2010). Because larval and juvenile stages need high amounts of P to build the P-rich RNA necessary for high somatic growth (Sterner and Elser 2002;Malzahn and Boersma 2012), they are more likely to be P-limited and face an excess of carbon than the fully grown adult stages.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The copepodites investigated in this present study showed increasing respiration rates with an increase of carbon in their food. Higher body-specific respiration rates in juvenile stages suggest that juvenile copepods use respiration to dispose of excess C as CO 2 and regulate their homoeostasis (He and Wang 2008;Laspoumaderes et al 2010;Darchambeau et al 2003), a pattern which has been reported from other juvenile zooplankton species (Jensen and Hessen 2007;Malzahn et al 2010). Because larval and juvenile stages need high amounts of P to build the P-rich RNA necessary for high somatic growth (Sterner and Elser 2002;Malzahn and Boersma 2012), they are more likely to be P-limited and face an excess of carbon than the fully grown adult stages.…”
Section: Discussionsupporting
confidence: 52%
“…Both of these pathways have been proposed as stoichiometric regulation mechanisms in herbivorous consumers fed on algae with high carbon-tonutrient ratios (e.g. Darchambeau et al 2003;Jensen and Hessen 2007;Malzahn et al 2010;Saba et al 2009). Disposing of surplus C by respiration is a common mechanism, reported from a range of aquatic consumers including Daphnia, the copepod A. tonsa and the flagellate Oxyrrhis marina (Hantzsche and Boersma 2010; Malzahn Jensen and Hessen 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In ecological research, the issue of nutrition quality and its effect on consumers has been the focus of attention for many years (Elser et al, 2000;Boersma et al, 2008;Malzahn et al, 2010). However, because most systems have been operated in an open condition, few studies have focused on closed ecological systems.…”
Section: Introductionmentioning
confidence: 99%